Challenges in Islamic Religious Education Learning among Diaspora Students at the Guidance School under the Indonesian School of Kuala Lumpur - Qurrata Akyuni; Wahyu Khafidah; Sabrina; Asriani; Ustad Ahsam Nawawi; Destia Natasya; Nisa Ul Humairah (Kodepena Indonesia, 2026)
Islamic Religious Education (IRE) plays a significant role in fostering students' faith, moral values, and character development. However, its implementation among Indonesian diaspora students at Sekolah Bimbingan (SB) Pandan Indah, Kuala Lumpur, encounters various challenges arising from the students' social, cultural, and residential environments. This study aims to analyze the challenges faced in the implementation of Islamic Religious Education for Indonesian diaspora students and to identify the strategies employed to address these challenges. The study adopted a qualitative approach using a case study design. Data were collected through interviews, observations, and document analysis involving teachers, students, and school administrators. The data were analyzed through data reduction, data display, and conclusion drawing, while triangulation was employed to ensure the trustworthiness of the findings. The results reveal that the major challenges in IRE learning include disparities in students' prior religious knowledge, limited instructional time, insufficient parental support due to work commitments, inadequate learning facilities, and the influence of the social environment and digital technology. To address these challenges, teachers implemented adaptive learning strategies, utilized digital learning media, provided gradual and individualized guidance, and strengthened communication with parents. The study concludes that the successful implementation of Islamic Religious Education for Indonesian diaspora students requires strong collaboration among schools, families, and the surrounding community to achieve the intended educational objectives effectively.